LINKING MATHEMATICS AND CULTURAL PRACTICES OF THE AGTA TABANGNON IN THE UPLAND COMMUNITIES OF GOA, PHILIPPINES - Salvador II Villar Briones; Shane Catolico Briones; Marieta Pelon Palmes (Ethnomathematics Journal, 2023)
The main foundation of ethnomathematics is an awareness of the many ways of knowing and doing mathematics that relate to the values, ideas, notions, procedures, and practices in a diversity of contextualized environments. The ethnomathematical practices of the Agta Tabangnon refer to the form of varying mathematical concepts that are embedded in their cultural practices. This paper presents the results of the efforts in documenting the ethnomathematics of the Agta Tabangnon in Sitio Ruras, Barangay Hiwacloy, Goa, Camarines Sur, Philippines. The significant contributions and challenges relative to their ethnomathematical concepts and cultural practices were also discussed. The Agta Tabangnon is a society that manifests stable cultural practices that capture and address every facet of their daily lives. Their ethnomathematics are instances of cultural practices that are passed down from generation to generation and have had a significant impact on society. Their ethnomathematics and cultural practices are the way their cultural group mathematizes their own realities in order to survive earnestly, so learning their practices is one way for us to embrace cultural diversity in our increasingly interconnected world.